2019
DOI: 10.1097/dcr.0000000000001287
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anastomotic Leak After Elective Colorectal Cancer Resection on Survival and Local Recurrence: A Propensity Score Analysis

Abstract: BACKGROUND: The occurrence of anastomotic leakage is still a life-threatening complication for patients after colorectal surgery. In literature not only an impact on the short-term outcome but also on long-term survival and local recurrence of colorectal cancer patients is discussed. OBJECTIVE: This study aimed to investigate the impact of anastomotic leakage on long-term survival and local recurrence. DESIGN: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
4
20
1
2
Order By: Relevance
“…In the current study, preoperative serum levels of CEA and CA19-9 and the incidence of anastomotic leakage were independently associated with worse RFS or OS following surgery for stage II colorectal cancer; consistent with the findings of previous studies (49)(50)(51). Identifying predictive biomarkers for the selection of patients with stage II colorectal cancer who could benefit from adjuvant chemotherapy are important.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, preoperative serum levels of CEA and CA19-9 and the incidence of anastomotic leakage were independently associated with worse RFS or OS following surgery for stage II colorectal cancer; consistent with the findings of previous studies (49)(50)(51). Identifying predictive biomarkers for the selection of patients with stage II colorectal cancer who could benefit from adjuvant chemotherapy are important.…”
Section: Discussionsupporting
confidence: 90%
“…A limitation of the algorithm used to assess recurrence is that it cannot distinguish between local recurrence and distant metastasis. However, the findings of our study are supported by a recent match‐paired analysis that found no difference in overall survival, DFS or local recurrence [29].…”
Section: Discussionsupporting
confidence: 86%
“…Finally, a low SAS was associated with POCs. POCs affect the prognosis in CRC because of marked postoperative in ammation and a poor immunological status [21,22]. In the present study, a lower SAS was signi cantly associated with severe POCs.…”
Section: Discussionsupporting
confidence: 50%